(untitled) (Research, Society and Development, 2025)
This article analyses video/projection mapping as a heritage-mediation device in historic centres and proposes guidelines for integrating it into Smart Tourism Destination (STD) strategies. We employed a multi-method design: an integrative literature review (2020–2025) with thematic analysis, and a documentary case study of activations in São Luís, Brazil (2019–2025). Findings indicate that the support-place, facades, squares and tilework, conditions legibility and sense of belonging; that aligning conservation, accessibility and urban routines mitigates spectacle effects and light/noise pollution; and that curation with local authorship plus public metadata (credits, licences, technical data) increases transparency and cultural value. We conclude that projection-mapping projects, when anchored in critical curation, social participation and impact assessment, can be integrated into STD policies oriented toward the right to the city and heritage preservation.